Job Satisfaction and Job Involvement among Non-Academic University Employees in Bangladesh - Sultana, Mst Sabiha; Dey, Biplob Kumar; Rahman, Abdur; Naher, Lutfun (Chittagong University Journal of Biological Sciences, 2024)
The need for skilled manpower in universities is immense to keep pace with the present changing modern world. Organizational factors like job satisfaction and job involvement have been identified as leading factors impacting skilled workforce in various organizations as well as in universities. The purpose of the present study was to explore the relationship between job satisfaction and job involvement of non-academic employees in Chittagong University in terms of job position and gender. The study was conducted on 180 respondents purposively selected from the registrar office, different halls, faculties, medical centre and the office of the various departments of the University of Chittagong. The age of the respondents ranged in between 22 and 62 years. The Bangla versions of job satisfaction scale and job involvement scale were used to collect the necessary data. The findings of the present study showed that job satisfaction of the first class non-academic employees of the university was greater than those of the third and fourth class employees (F = 11.69, df = 2/ 174, p < .001). Consistent with this, job involvement of the first class non-academic employees was found to be greater than the third and fourth class employees (F = 6.81, df = 2/ 174, p < .001). A significant positive correlation between job satisfaction and job involvement of non-academic employees was also evident (r = .47, p < .01). The Chittagong Univ. J. B. Sci., Vol. 10(1 &2):201-216, 2020